Early influenza virus exposure shapes the B cell response to influenza vaccination in individuals 50 years later - Spangler, Abby; Shimberg, Geoffrey D.; Mantus, Grace E.; Malek, Rory; Cominsky, Lauren Y.; Tsybovsky, Yaroslav; Li, Ning; Gillespie, Rebecca A.; Ravichandran, Michelle; Creanga, Adrian; Raab, Julie E.; Gajjala, Suprabhath R.; et al. (Immunity (Cambridge, Mass.), 2025)
Pre-existing immunity impacts vaccine responses to influenza, but directly connecting influenza infections early in life with immune responses decades later is difficult. However, H2N2 stopped circulating in the human population in 1968, creating the opportunity to directly evaluate the impact of early H2N2 exposure on vaccine responses 50 years later. Here, we vaccinated individuals born before (H2 exposed) or after (H2 naive) 1968 with an H2 hemagglutinin (HA) DNA plasmid and/or a ferritin nanoparticle vaccine. H2-exposed individuals generated a rapid B cell recall response that was more potent, targeted more conserved epitopes, and differed phenotypically from the de novo response in H2-naive individuals. Furthermore, vaccinating with a DNA versus a protein nanoparticle vaccine altered the response in H2-naive but not H2-exposed individuals. This study establishes and describes the lifelong impact of influenza HA-specific memory B cells formed early in life on vaccine responses decades later. [Display omitted] •H2-specific B cells are maintained for 50 years and recalled upon vaccination•IgA memory recall responses preferentially target conserved HA head epitopes•Steady-state long-lived memory B cells have an atypical memory phenotype•The de novo, but not recall, B cell response varies with different vaccine platforms To understand the influence and longevity of early influenza imprinting, Spangler et al. investigate the response to an H2 HA vaccine in individuals with and without exposure to H2N2 virus 50 years ago. They find that those with prior exposure have a robust recall response of pre-existing H2-specific memory B cells established decades ago, with no detectable de novo response.